Hierarchical power control model for interference mitigation in a two – Tier heterogeneous network. Issue 1 (1st January 2019) - Ladipo, O. I.; Gbenga-Ilori, A. O.
Abstract: The heterogeneous deployment of different base stations has increased the overall network capacity and reduced excess traffic from the macrocell network. However, this improved system performance is accompanied by several technical challenges which include interference management, power control, resource allocation, security, backhaul, and handover issues. This paper presents a single-leader, multi-follower power control game model that mitigates interference in a two-tier heterogeneous network where femtocells are densely deployed within the coverage area of the macrocell. In the proposed game, the femtocells act as the followers and update their respective transmission power based on the information received from the macrocell which is the leader of the Stackelberg game. The existence of the Stackelberg equilibrium (SE) in the formulated game was determined by the backward induction method and it showed the possibility of a stability point that is optimal and Pareto efficient. Extensive simulations were carried out to evaluate the performance of the proposed scheme and the effect of the set transmission cost and utility function on the base stations. Simulation results showed a reduced level of interference between the base stations, improved network capacity, and effective allocation of network resources among the users.